The Inheritance of Saronen Instrument in Sumenep, Madura - Ni Made Ruastiti; Rino Ega Vebrian; I Ketut Sariada (Bina Nusantara University, 2020)
The research aimed to discuss the position and function of the saronen instrument in Sumenep, Madura. Saronen, as one of the cultural heritage of the Madurese people, was still preserved. The research questions were: (1) what was the position of the saronen instrument in the culture of the Madurese people? (2) How was the strategy for the inheritance of the instrument carried out by the people of Sumenep, Madura? The research was conducted using qualitative methods. The data collection process was carried out through observation, literature study, and interviews with ten informants. Data analysis was carried out in a descriptive qualitative manner using semiotic theory and structural-functional theory. The results show (1) the saronen instrument has an important position in the culture of the Madurese people, including Madurese ethnic identity, as a public relations media, and the branding of Sumenep as a tourist destination in East Java. The saronen instrument, which is originally used as a da'wah medium, has now developed as a musical accompaniment to the activities of the sapi sono and karapan sapi contest and entertainment medium for the Madurese people in celebratory events and government events. (2) The inheritance strategy of the saronen instrument is carried out by the indigenous people through a vertical system, namely an inheritance system through a genetic mechanism passed down from time to time across generations and a horizontal system, namely inheritance through institutions, including educational institutions such as schools and art studios.